Basic skills of psychosocial support - Shablevska, Tetiana (Psychosomatic Medicine and General Practice, 2023)
This text is the theses for the qualifying graduation thesis on the topic "Basic skills of psychosocial support". The following is devoted to the effectiveness of teaching basic psychosocial skills in humans.